Frontoparietal theta activity supports behavioral decisions in movement-target selection - Rawle, Christian; Miall, Chris; Praamstra, Peter (Frontiers in Human Neuroscience, 2012)
There is recent EEG evidence describing task-related changes of theta power in spatial attention and reaching/pointing tasks. Here, we aim to better characterize this theta activity and determine whether it is associated with visuospatial memory or with visuospatial selection functions of the frontoparietal cortex. We recorded EEG from 20 participants during a movement precuing task with centre-out joystick movements. Precues displayed 1, 2, or 4 potential targets and were followed (SOA 1.2 s) by a central response cue indicating the movement target. Remembering the precued target location(s) was mandatory in one and optional in a second version of the task. Analyses evaluated two slow brain potentials (CNV, contingent negative variation and CDA, contralateral delay activity) and task-related power changes. Results showed a differential modulation of frontal CNV and parietal CDA, consistent with earlier described set-size effects on motor preparation and visual short-term memory. Short-lived phases of theta synchronization (ERS) were found 150-500 ms after precue and response cue presentation, exhibiting parietal and frontal maxima. The increase of frontoparietal theta power following response cue presentation was strongly modulated by target load, i.e. absent for 1-target (when the movement target could be selected in advance), contrasting with a robust 20-50% ERS response in 2- and 4-target conditions. The scalp distribution, the timing, and the modulation by set-size suggest a role of theta activity in movement target selection. The results support a recently proposed view of theta as emerging around behavioral decision points, linked to the evaluation of choice-relevant information.